Assessing student learning a common sense guide - Suskie, Linda A. (San Francisco, CA Jossey-Bass, 2018)
Assessing Student Learning is a standard reference for college faculty and administrators, and the third edition of this highly regarded book continues to offer comprehensive, practical, plainspoken guidance. The third edition adds a stronger emphasis on making assessment useful; greater attention to building a culture in which assessment is used to inform important decisions; an enhanced focus on the many settings of assessment, especially general education and co-curricula; a new emphasis on synthesizing evidence of student learning into an overall picture of an integrated learning experience; new chapters on curriculum design and assessing the hard-to-assess; more thorough information on organizing assessment processes; new frameworks for rubric design and setting standards and targets; and many new resources. Faculty, administrators, new and experienced assessment practitioners, and students in graduate courses on higher education assessment will all find this a valuable addition to their bookshelves.
What is assessment? -- The many settings for student learning and assessment -- What are effective assessment practices? -- Learning goals : articulating what you most want students to learn -- Designing curricula to help students learn what's important -- How will your evidence of student learning be used? -- Planning assessments in academic programs -- Planning assessments in general education, co-curricula, and other settings -- Guiding and coordinating assessment efforts -- Helping everyone learn what to do -- Supporting assessment efforts -- Keeping assessment cost-effective -- Collaborating on assessment -- Valuing assessment and the people who contribute -- Designing rubrics to plan and assess assignments -- Creating effective assignments -- Writing multiple-choice and other objective tests -- Assembling evidence of student learning into portfolios -- Selecting published instruments -- Other assessment tools -- Assessing the hard-to-assess -- Setting meaningful standards and targets -- Summarizing and storing evidence of student learning -- Analyzing evidence of student learning -- Sharing evidence of student learning -- Using evidence of student learning to inform important decisions.
Includes bibliographical references and index.
Keywords: College students -- Rating of; Educational tests and measurements; Educational Measurement; Competency-Based Education